2022
DOI: 10.1007/s10853-022-07558-1
|View full text |Cite
|
Sign up to set email alerts
|

Review of advanced techniques for manufacturing biocomposites: non-destructive evaluation and artificial intelligence-assisted modeling

Abstract: Natural fiber reinforced polymer composites (NFRPCs) are being widely used in aerospace, marine, automotive, and healthcare applications due to their sustainability, low cost and ecofriendly nature. The NFRPCs manufactured through conventional, and computer controlled intelligent manufacturing techniques may contain internal and external defects. Traditionally, the microstructure of NFRPCs at different stages of manufacturing was obtained using destructive techniques which have stringent sample size restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 311 publications
(315 reference statements)
0
17
0
Order By: Relevance
“…Natural fiber-reinforced polymer composites are being widely used in aerospace, marine, automotive, and health care applications due to their sustainability, low cost, and ecofriendly nature. These composites can be manufactured through conventional and advanced manufacturing techniques to avoid internal and external defects [ 20 ]. The optimization of process parameters of composite manufacturing techniques is essential for manufacturing high-quality components.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fiber-reinforced polymer composites are being widely used in aerospace, marine, automotive, and health care applications due to their sustainability, low cost, and ecofriendly nature. These composites can be manufactured through conventional and advanced manufacturing techniques to avoid internal and external defects [ 20 ]. The optimization of process parameters of composite manufacturing techniques is essential for manufacturing high-quality components.…”
Section: Introductionmentioning
confidence: 99%
“…When self-healing epoxy composite embedded with HGF as a healing agent and underwent indentation and a three-point flexural test and results confirmed that there is good strength recovery in the composite after healing. These investigations stated that self-healing HGF polymers have strong potential and can be used for aerostructures [ 196 , 215 ].…”
Section: Fiber-reinforced Epoxy Self-healing Compositesmentioning
confidence: 99%
“…Natural fibers are also used to make insulation materials for a variety of applications, including blowing insulation, pouring insulation, impact sound insulation materials, and ceiling panels for thermal insulation and acoustic isolation. 21 Natural fiber composites have a promising future, even outperforming current materials.…”
Section: Introductionmentioning
confidence: 99%